Breaking Language Barriers: Amplifying Arabic Proficiency in Bilingual Environment through Immersive Learning - Murtadho, Muhammad Alfa Choirul; Thohir, Muhammad; Yusuf, Kamal; Rif'at, Ahmad Dzulkifli (Universitas Ahmad Dahlan, 2025)
Arabic language teaching in Indonesia continues to face persistent challenges, particularly in fostering student’s practical and communicative competencies. One promising approach to addres this issue is language immersion, which places learners in environments that simulate native Arabic usage. This article delves into explores the implementation of language immersion in Arabic learning within bilingual environment settings. Using a qualitative case study design, data were collected through interviews, participatory observations, and document analysis, including syllabi and records of learning activities. The analysis followed the BJOG Perspectives on Qualitative Research framework, encompassing stages of initial coding, thematic categorization, and reflective narrative interpretation. Results demonstrate that language immersion significantly enhances students' Arabic proficiency, particularly in speaking, listening, and active participation. Student exhibited increased confidence in using Arabic not only in formal classroom contexts but also in everyday interactions. These outcomes underscore the importance of sustained language exposure, authentic social interaction, and context-rich learning in second language acquisition. This study offers a novelty contribution by highlighting how language immersion is applied in the distinctive environment of bilingual pesantren, where classroom instruction is integrated with students’ daily routines. The synergy between structured academic activities and natural language use in dormitory life fosters a comprehensive and continuous learning experience. This model, blending formal instruction with informal immersion, remains underexplored in prior research and presents a valuable framework for Arabic language education in similar contexts.